2012
DOI: 10.3904/kjim.2012.27.3.278
|View full text |Cite
|
Sign up to set email alerts
|

Role of Photodynamic Therapy in the Palliation of Obstructing Esophageal Cancer

Abstract: Background/AimsThe aim of this non-randomized study was to determine the role of photodynamic therapy (PDT) in a multimodal approach for the palliation of advanced esophageal carcinoma.MethodsTwenty consecutive patients with obstructing esophageal cancer were enrolled in this study. Each subject had dysphagia, and nine could not swallow fluid. External beam radiotherapy or a self-expandable metal stent was used following PDT for dysphagia due to recurrence of the malignancy.ResultsAt 4 weeks post-PDT, a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 20 publications
(24 reference statements)
1
16
0
3
Order By: Relevance
“…Photodynamic therapy (PDT) is a novel oncotherapy exerting a selective cytotoxic activity toward malignant cells via reactive oxygen species (ROS) generated by energy transduction from photosensitizers after excitation by visible light. Photofrin was the first photosensitizer approved by FDA in 1995 and Photofrin‐mediated PDT is the most widely used for reducing obstruction and relieving symptoms in patients with obstructing esophageal cancer . In spite of promising initial treatment responses after PDT, 5‐year recurrence rate remains at high level .…”
Section: Introductionmentioning
confidence: 99%
“…Photodynamic therapy (PDT) is a novel oncotherapy exerting a selective cytotoxic activity toward malignant cells via reactive oxygen species (ROS) generated by energy transduction from photosensitizers after excitation by visible light. Photofrin was the first photosensitizer approved by FDA in 1995 and Photofrin‐mediated PDT is the most widely used for reducing obstruction and relieving symptoms in patients with obstructing esophageal cancer . In spite of promising initial treatment responses after PDT, 5‐year recurrence rate remains at high level .…”
Section: Introductionmentioning
confidence: 99%
“…This technique has resulted in regression and, in some cases, complete reversal of BE [7-10]. Since then, some studies of patients with esophageal dysplasia and cancer have reported that complete remission (CR) can be achieved in superficial lesions using PDT (Table 1) [11-19]. Studies on the use of PDT for esophageal squamous cell carcinoma (SCC) confined to the mucosal layer have suggested that PDT can be used as an alternative to esophagectomy given the low risk of lymph node metastasis in these patients.…”
Section: Esophageal Cancermentioning
confidence: 99%
“…Несмотря на появление новых методов диагностики и лечения рака пищевода на ранних стадиях в последние годы, частота выявления больных с РП на III-IV стадиях заболевания по-прежнему остается очень высокой и составляет более 67% [2]. Важным показателем злокачественности течения рака пищевода являются низкие показатели 5-летней выживаемости, не превышающие 10-15% как в России, так и в странах Европы [3]. В половине случаев основным клиническим симптомом рака пищевода является дисфагия, возникающая при сужении просвета на 50-70% [4], когда возможности хирургического, лучевого, комбинированного и комплексного лечения ограничены [1,2,5].…”
Section: Introductionunclassified